Landasan Sosiokultural dalam Kurikulum Pendidikan Agama Islam - Irfan Ismail; Mulyawan Safwandy Nugraha; Asep Nursobah (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
Indonesia's diverse society requires tolerance, but paradoxically, we also see the emergence of intolerance, radicalism, and extremism, especially among millennials, who are very worrying even though schools are always taught to respect their cultural and social backgrounds. Therefore, it is necessary to build a moderate understanding to overcome this problem. With this background, researchers feel interested in exploring how sociocultural foundations in the Islamic religious education curriculum. This research uses qualitative field methods with a phenomenological approach. Looking at the social and cultural aspects of society, in the educational environment such as participation in social and religious activities. Religious tolerance that exists in the millennial generation family education that has been passed down from generation to generation by their parents. Keywords: Sociocultural; Curriculum; Islamic Religious Education